2008
DOI: 10.1038/modpathol.2008.33
|View full text |Cite
|
Sign up to set email alerts
|

Altered eIF6 and Dicer expression is associated with clinicopathological features in ovarian serous carcinoma patients

Abstract: MicroRNAs are a group of small non-coding RNAs approximately 22 nucleotides in length. Recent work has shown differential expression of mature microRNAs in human cancers. Production and function of microRNAs require coordinated processing by proteins of the microRNA machinery. Dicer and Drosha (RNase III endonucleases) are essential components of the microRNA machinery. Recently, the ribosome anti-association factor eIF6 has also been found to have a role in microRNA-mediated post-transcriptional silencing. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
93
2
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 52 publications
13
93
2
2
Order By: Relevance
“…Recently, dysregulation of Dicer in malignancies has been of great interest in oncology. Studies have shown that Dicer is upregulated in prostate adenocarcinomas, ovarian serous carcinomas, esophageal cancers and acute myeloid leukemia (AML), and downregulated in hepatocellular carcinomas, lung cancers and ovarian carcinomas (17)(18)(19). The present study showed that Dicer was downregulated in TCCs compared to their NAT samples or normal bladder mucosae.…”
Section: Discussionsupporting
confidence: 54%
“…Recently, dysregulation of Dicer in malignancies has been of great interest in oncology. Studies have shown that Dicer is upregulated in prostate adenocarcinomas, ovarian serous carcinomas, esophageal cancers and acute myeloid leukemia (AML), and downregulated in hepatocellular carcinomas, lung cancers and ovarian carcinomas (17)(18)(19). The present study showed that Dicer was downregulated in TCCs compared to their NAT samples or normal bladder mucosae.…”
Section: Discussionsupporting
confidence: 54%
“…19 Furthermore, our group has demonstrated dysregulation of Dicer and Drosha proteins (both of which coordinate micro-RNA processing) in ovarian serous carcinoma. 64 Recent research suggests that DNA methylation may also be involved in the regulation of microRNA expression in ovarian cancer, and the methylation can be reversed by DNA methyltransferase inhibitors. 9,65 Indeed, microRNA control and deregulation may be more complex as widespread microRNA repression by transcription factors such as c-myc (that targets miR-195/miR-497) have also been found to contribute to tumourigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Forced expression of miR-143 and miR-145 inhibit cell growth in cervical cancer cells (Wang et al, 2008). Although the biological function of miR-195 and miR-497 has not been characterised, reduced expression of miR-195 and miR-497 on the 17p13 locus has been documented in primary peritoneal carcinoma (Flavin et al, 2008).…”
Section: Discussionmentioning
confidence: 99%